Determination the Optimum Conditions for Antibiotics Production from Streptomyces albus that Locally Isolated - H. Abdull Wahaab, Marwa (Tikrit Journal of Pharmaceutical Sciences, 2023)
A total of 31 different Streptomyces isolates were recovered from 25 samples of soil collected from different sites in Tikrit University gardens. There were 14 isolates showed as activity against pathogenic bacterial isolates, 6 (43)% isolates were effected against Staph. aureus. and E. coli, while 3 (21)% isolates showed impact high against Staphylococcus aureus only, and did not show any effect against Escherichia coli, while 5 (36)% isolates showed impact against E. coli only, Streptomyces albus were identified which gave the high effectiveness against pathogenic bacteria on the bases of morphological and biochemical tests and sensitivity to some antibiotics. This isolate was gave high production at 30 C for 7 days and pH 7, the best carbon source when used glucose at concentrations 15-20 g / l and the level of salt was at 1.5 g / l and with the use of Cysteine as a nitrogen source oncluded that AEA has a therapeutic activity against nephrotoxicity induced by gentamicin in male rats.